Silicon nanoparticles for battery, and method for manufacturing silicon-doped electrode material

JP2025009698AInactive Publication Date: 2025-01-20NANYA PLASTICS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023193295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2023-11-13
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0021】 以上のように、本発明のバッテリー用シリコンナノ粒子の製造方法において、分散剤の添加により、シリコンナノ粒子は、結合や凝集が難しくなるため、それにより、粉砕効率が向上し、シリコン原料の微細化が促進される。アルカリ溶液の添加により、バッテリー用シリコンナノ粒子の表面にシリコン酸化物層を形成することができるため、それにより、バッテリー用シリコンナノ粒子の体積膨張が抑制される。上記のバッテリー用シリコンナノ粒子で調製されたシリコンドープ電極材料は、複数回の充放電サイクルを経たシリコンドープ電極材料の容量保持率を効果的に改善することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009698000001_ABST
    Figure 2025009698000001_ABST
Patent Text Reader

Abstract

To provide a silicon nanoparticles for battery and a method for manufacturing a silicon-doped electrode material.SOLUTION: A method for manufacturing silicon nanoparticles for battery includes the following steps. Dispersant and solvent are mixed to form dispersion liquid. Then, the dispersion liquid, pulverization medium, and a silicon material is added to pulverizer. Pulverization processing is performed to form silicon nanoparticles having an average particle size of less than 200nm. Then, silicon dispersion liquid containing silicon nanoparticles is taken out. Then, alkaline solution is added to the silicon dispersion liquid to form silicon nanoparticles for battery. Each surface layer of the silicon nanoparticles for battery is a silicon oxide layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing electrode materials, and in particular to a method for producing silicon nanoparticles and silicon-doped electrode materials for batteries. [Background technology]

[0002] Currently, graphite is the predominant anode material in commercial lithium-ion batteries. However, developments in this material are approaching its theoretical capacity of 372 milliampere-hours per gram (mAh / g). For future applications requiring high energy density, the space that graphite can offer is quite limited.

[0003] Silicon-based anodes, as the most promising next-generation anode material, have the advantage of high theoretical capacity (4200mAh / g). However, silicon cannot form an anode by itself, because silicon undergoes violent volume expansion during the charging and discharging process, causing material pulverization and cycle life degradation. Silicon is usually mixed with graphite material to form silicon-doped carbon electrodes. Also, considering the stability of the battery, the silicon content is about 3%-5% of the total weight of the silicon-doped carbon electrode material.

[0004] Among the known solutions, a common method is to use nanotechnology to minimize the size of silicon materials and to use nanoscale silicon to control the volume expansion of silicon materials. Silicon materials available on the market are available in sizes ranging from 10 nm to 300 nm, but are expensive. Furthermore, nanoscale silicon materials are prone to agglomeration into large particles, making it difficult to uniformly mix silicon with other materials during the electrode manufacturing process.

[0005] Therefore, improving the existing processes for producing silicon materials that can alleviate the volume expansion problem and improve the cycle life of silicon-doped electrode materials has become an urgent problem in the industry. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a method for producing silicon nanoparticles and silicon-doped electrode materials for batteries, which have the advantage of mitigating volume expansion, thereby improving the capacity retention of the silicon-doped electrode materials after multiple charge-discharge cycles. [Means for solving the problem]

[0007] The manufacturing method of silicon nanoparticles for batteries in the present invention includes the steps of mixing a dispersant and a solvent to form a dispersion, adding the dispersion, a grinding medium and a silicon raw material to a grinder, carrying out a grinding process to form silicon nanoparticles with an average particle size of less than 200 nm, extracting the silicon dispersion containing the silicon nanoparticles, and adding an alkaline solution to the silicon dispersion to form silicon nanoparticles for batteries, and each surface layer of the silicon nanoparticles for batteries is a silicon oxide layer.

[0008] In one embodiment of the present invention, the silicon raw material is a recycled silicon material.

[0009] In one embodiment of the present invention, the dispersing agent is at least one selected from polyethylene glycol, polyvinylpyrrolidone, triethylhexyl phosphate, sodium lauryl sulfate, methylpentanol, cellulose derivatives, polyacrylamide, and polyethylene glycol fatty acid.

[0010] In one embodiment of the invention, the solvent is water, an alcohol solvent, or a ketone solvent.

[0011] In one embodiment of the present invention, the amount of the dispersant added to the pulverizer is 10 to 50 parts by weight with respect to 100 parts by weight of the silicon raw material added.

[0012] In one embodiment of the present invention, the grinding media are spherical in shape and have an average particle size of 100 nm to 500 nm.

[0013] In one embodiment of the present invention, the amount of the grinding medium added is 100 to 500 parts by weight per 100 parts by weight of the silicon raw material added.

[0014] In one embodiment of the invention, the alkaline solution is a lithium hydroxide solution, a sodium hydroxide solution, or a potassium hydroxide solution.

[0015] In one embodiment of the present invention, the amount of the alkaline solution added is 0.1 to 5 parts by weight with respect to 100 parts by weight of the silicon nanoparticles added.

[0016] In one embodiment of the present invention, the grinding process is a wet ball grinding method, and the grinding time of the grinding process is 2 hours to 6 hours.

[0017] In one embodiment of the present invention, the ratio of the particle size of the silicon nanoparticles for batteries to the thickness of the silicon oxide layer is 3:1 to 40:1.

[0018] In one embodiment of the present invention, the silicon oxide layer has a thickness of 5 nm to 30 nm.

[0019] The manufacturing method of the silicon-doped electrode material in the present invention includes the steps of providing silicon nanoparticles for batteries obtained by the manufacturing method described in claim 1, mixing the silicon nanoparticles for batteries with an active material, and performing spray granulation and calcination to obtain a silicon-doped electrode material, wherein the active material is a carbon material, a metal element, or a metal alloy compound.

[0020] In one embodiment of the present invention, the content of the silicon nanoparticles for batteries is 1 wt% to 40 wt% based on the total weight of the silicon-doped electrode material. Effect of the Invention

[0021] As described above, in the method for producing silicon nanoparticles for batteries of the present invention, the addition of a dispersant makes it difficult for silicon nanoparticles to bond or aggregate, thereby improving the pulverization efficiency and promoting the refinement of silicon raw materials. The addition of an alkaline solution can form a silicon oxide layer on the surface of the silicon nanoparticles for batteries, thereby suppressing the volume expansion of the silicon nanoparticles for batteries. The silicon-doped electrode material prepared with the above silicon nanoparticles for batteries can effectively improve the capacity retention rate of the silicon-doped electrode material after multiple charge-discharge cycles.

[0022] In order to make the above easier to understand, several embodiments are described in detail below in conjunction with the drawings. [Brief description of the drawings]

[0023] The accompanying drawings are included to provide a further understanding of the principles of the invention, and are incorporated in and constitute a part of this specification. The drawings illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0024] [Figure 1] 1 is a flow chart of a method for producing silicon nanoparticles for batteries in the present invention. [Figure 2A] 1 is an electronic image of a slice of silicon-doped carbon electrode material in accordance with the present invention. [Figure 2B] Analysis of the elemental composition of the circled area in Figure 2A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are merely illustrative and do not limit the present invention.

[0026] Here, ranges expressed as "one value to another value" are a summary method to avoid listing every value in the range in the specification. Thus, the description of a particular numerical range includes any value in that numerical range and smaller numerical ranges defined by any value in that numerical range, and is the same as if the any value and the smaller numerical range were specified in the specification.

[0027] FIG. 1 is a flow chart of a method for manufacturing silicon nanoparticles for batteries in the present invention. Referring to FIG. 1, step S102 is carried out to mix a dispersant and a solvent to form a dispersion liquid. The dispersant may be, for example, an organic dispersant. Specifically, the dispersant may be at least one selected from polyethylene glycol, polyvinylpyrrolidone, triethylhexyl phosphate, sodium lauryl sulfate, methylpentanol, cellulose derivatives, polyacrylamide, and polyethylene glycol fatty acid, but the present invention is not limited thereto. The dispersant may be, for example, a polymer such as polyethylene glycol or polyvinylpyrrolidone. The solvent may be, for example, water, an alcohol solvent, or a ketone solvent.

[0028] Next, step S104 is carried out, and the dispersion liquid, the grinding medium, and the silicon raw material are added to the grinder. In this embodiment, the prepared dispersion liquid and the grinding medium are added together to the grinder, and then the silicon raw material is added. In some other embodiments, the dispersion liquid, the grinding medium, and the silicon raw material may be added together to the grinder. The present invention does not limit the order of addition to the grinder.

[0029] In this embodiment, the silicon raw material may be regenerated silicon processed by the purification and recovery process of silicon waste. The silicon waste may be, for example, discarded solar cells, IC boards, silicon wafer waste, memory cards, etc. The silicon raw material is a recycled silicon material, and therefore has the advantages of being environmentally friendly and low-cost.

[0030] The grinding media is used to grind the silicon raw material into silicon nanoparticles. The shape, size, and material of the grinding media are related to the nature of the material to be ground, the supply requirements, and the product particle size. In this embodiment, the shape of the grinding media is, for example, spherical, and the average particle diameter (D 50 ) is, for example, 100 nanometers (nm) to 500 nm, and the material may be, for example, zirconia, but the present invention is not limited thereto. The amount of grinding media added is related to the size of the grinding chamber in the grinder and the amount of the material to be ground. In some embodiments, the amount of grinding media added may be, for example, 100 to 500 parts by weight, relative to 100 parts by weight of the silicon raw material added. When the amount of grinding media added is within the above range, the silicon raw material can be effectively ground into silicon nanoparticles of the desired particle size in the subsequent step (for example, the particle size can be made less than 200 nm). When the amount of grinding media added is less than 100 parts by weight, the area where the grinding media can contact the material to be ground is small, so a lot of grinding time is required and the grinding effect is poor. When the amount of grinding media added is more than 500 parts by weight, in order to avoid damaging the machine during grinding, the dispersion needs to be excessively diluted to fill the grinding chamber, which does not meet the solid content required for practical use.

[0031] The dispersant can be used to disperse silicon nanoparticles to prevent aggregation and prevent the overall viscosity from becoming too high to continue grinding, which helps improve grinding efficiency. In some embodiments, the amount of dispersant added to the grinder may be, for example, 10 to 50 parts by weight relative to 100 parts by weight of the silicon raw material. In other embodiments, the amount of dispersant added to the grinder may be, for example, 20 to 40 parts by weight relative to 100 parts by weight of the silicon raw material. When the amount of dispersant added is less than 10 parts by weight, the effect of preventing aggregation of silicon nanoparticles may be reduced. When the amount of dispersant added is more than 50 parts by weight, it may make subsequent purification difficult.

[0032] Next, step S106 is performed to perform a grinding process to form silicon nanoparticles with an average particle size of less than 200 nm. In this embodiment, the grinding process is a wet ball mill method, and the grinding time can be adjusted according to the desired particle size. Specifically, a particle size analyzer can be used to measure the average particle size of the current silicon particles during the grinding process. In some embodiments, the grinding time can be, for example, 2 to 6 hours (h), but the present invention is not limited thereto. In addition, a dispersion liquid can be added during the grinding process to improve the grinding efficiency. Here, the total amount of the dispersant added (i.e., the sum of the amount of the dispersant added to the grinder before and during grinding) does not exceed 50% by weight of the silicon raw material.

[0033] Next, step S108 is performed to extract the silicon dispersion liquid containing silicon nanoparticles.

[0034] Next, step S110 is carried out to add an alkaline solution to the silicon dispersion liquid to form silicon nanoparticles for batteries. Each surface layer of the silicon nanoparticles for batteries is a silicon oxide layer. In this embodiment, the alkaline solution can oxidize the surface layer of the silicon nanoparticles to form silicon nanoparticles for batteries having a silicon oxide layer on the surface. In some embodiments, the thickness of the oxide layer on the surface of the silicon nanoparticles for batteries may be, for example, 5 to 30 nm. The silicon oxide layer on the surface of the silicon nanoparticles for batteries can suppress the volume expansion of the silicon inside, thereby enabling an electrode formed of silicon nanoparticles for batteries doped with other active materials (e.g., carbon materials, metal elements, or metal compounds) to maintain its capacity even after multiple charge and discharge cycles. Here, the manufacture of silicon nanoparticles for batteries is completed. This rapid volume expansion causes the silicon to be crushed and broken, and peeled off from the plate, resulting in capacity loss and reduced cycle life.

[0035] In detail, silicon has a theoretical capacity of up to 4200mAh / g, but the main reason why silicon electrodes have not yet been commercialized is that when lithium and silicon form a lithium-silicon alloy phase, the volume expands to 300-400% of the original volume. This rapid volume expansion causes silicon to be crushed and peeled off from the plate, resulting in capacity loss and cycle life reduction. The theoretical capacity of silicon oxide is 1547mAh / g. Although the capacity of silicon oxide is not as high as that of silicon, the volume expansion of silicon oxide (about 134%) is smaller than that of silicon. And silicon oxide has a better capacity retention. In the present invention, by adding a small amount of alkali, the surface layer of silicon nanoparticles can be oxidized to a silicon oxide layer, thereby suppressing the volume expansion of silicon and improving the capacity retention.

[0036] In some embodiments, the alkaline solution is, for example, a lithium hydroxide solution, a sodium hydroxide solution, or a potassium hydroxide solution, and the pH value of the alkaline solution is 8 to 13. In some embodiments, the amount of the alkaline solution added may be, for example, 0.1 to 5 parts by weight relative to 100 parts by weight of the amount of silicon nanoparticles added. In some other embodiments, the amount of the alkaline solution added may be, for example, 0.5 to 2 parts by weight relative to 100 parts by weight of the amount of silicon nanoparticles added. The amount of the alkaline solution added is related to the thickness of the silicon oxide layer on the surface of the silicon nanoparticles for batteries. When the amount of the alkaline solution added is less than 0.1 parts by weight, the oxidation effect on the silicon nanoparticles is negligible. When the amount of the alkaline solution added is more than 5 parts by weight, the thickness of the silicon oxide layer increases (more silicon is oxidized). The increase in the thickness of the oxide layer can more effectively suppress the volume expansion of silicon, but the capacity of the silicon oxide is smaller than that of silicon, so the capacity of the silicon-doped electrode material formed thereafter is greatly reduced. When the amount of the alkaline solution added is within the above range, the silicon-doped electrode material can have high capacity and excellent capacity retention at the same time. In this case, the ratio of the particle diameter of the silicon nanoparticles for batteries to the thickness of the silicon oxide layer may be, for example, 3:1 to 40:1.

[0037] In the present invention, the silicon nanoparticles for batteries can be mixed with an electrode active material to form a silicon-doped electrode material. Specifically, the method for producing the silicon-doped electrode material can include the following steps: Provide the silicon nanoparticles for batteries described above. Then mix the silicon nanoparticles for batteries with an active material. Then, perform spray granulation and calcination to obtain the silicon-doped electrode material. In some embodiments, the active material can be, for example, a carbon material, a metal element, or a metal compound. The carbon material can be graphite or other carbon sources, the metal element can be tin, nickel, titanium, manganese, copper, or magnesium, and the metal compound can be titanium carbide or titanate, but the present invention is not limited thereto.

[0038] The silicon-doped electrode material can be used as the negative electrode of a battery. The calcination process is carried out after injecting an inert gas, which may be, for example, argon, and the calcination temperature may be, for example, 700-900 degrees. In the present invention, the calcination process can effectively crack and remove the dispersant / organic material to prevent it from affecting the electrical properties of the electrode material. In some embodiments, the content of the silicon nanoparticles for the battery is 1-40 wt% relative to the total weight of the silicon-doped electrode material. When the content of the silicon nanoparticles for the battery is less than 1 wt%, the content is too small, which is equivalent to not doping the battery material with silicon, so the effect of improving the capacity of the electrode material is not good. When the content of the silicon nanoparticles used in the battery is more than 40 wt%, the stability of the battery may be reduced.

[0039] The following embodiments are provided to illustrate the method for producing silicon nanoparticles and silicon-doped electrode materials for batteries of the present invention, but the following embodiments are not intended to limit the scope of the present invention.

[0040] Embodiment

[0041] To demonstrate that the silicon nanoparticles proposed in the present invention for batteries can effectively maintain the capacity of the electrodes, the following specific embodiments are provided.

[0042] Embodiment 1 Relationship between the average particle size of silicon nanoparticles, the amount of dispersant added, and the grinding time

[0043] 1.1 Preparation of silicon nanoparticles for batteries

[0044] Dispersants (polyethylene glycol and polyvinylpyrrolidone) are dissolved in water to form a dispersion. Next, the dispersion and grinding media are fed together into a grinder, and silicon raw material is added and ground to form silicon nanoparticles. After that, the ground silicon dispersion is discharged and taken out, and an appropriate amount of alkaline solution (lithium hydroxide) is added, mixed and reacted to prepare silicon nanoparticles for batteries in Examples 1 to 5. The amounts of silicon raw material, dispersant, grinding media, and alkaline solution added, and the grinding time are as shown in Table 1.

[0045] 1.2 Mean particle size measurement and results

[0046] The average particle size (D) of silicon nanoparticles for batteries in Examples 1 to 5 was measured using a particle size analyzer. 50 The results are shown in Table 1.

[0047] [Table 1]

[0048] As can be seen from Table 1, with increasing addition of dispersant and extending the grinding time, the average particle size of silicon nanoparticles for batteries can be gradually reduced.

[0049] Example 2 Elemental analysis of silicon-doped carbon electrode material

[0050] 2.1 Preparation of silicon-doped carbon electrode material

[0051] The silicon nanoparticles for batteries of Example 1 are mixed with graphite, then spray granulation is carried out, and then inert gas (argon) is introduced to carry out calcination, to obtain the silicon-doped carbon electrode material of Example 6.

[0052] 2.2 TEM-EDS analysis and results

[0053] The silicon-doped carbon electrode material of Example 6 was sliced. Then, the structure and elemental analysis was carried out by transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS). The results are shown in Figures 2A and 2B.

[0054] FIG 2A is an electron image of a slice of the silicon-doped carbon electrode material of the present invention. FIG 2B is an analysis of the elemental composition of the circled area in FIG 2A. By referring to FIG 2A and FIG 2B simultaneously, it can be seen that the content of silicon (Si) is relatively high compared to the content of oxygen (O), and the silicon lattice image can be observed under high resolution images, so it can be inferred that silicon is only partially oxidized, and carbon (C) and silicon are alternately stacked to form a composite structure.

[0055] Embodiment 3 Capacity Retention of Silicon-Doped Carbon Anode Half-Cell

[0056] 3.1 Half-cell assembly

[0057] By adjusting the amount of alkaline solution added (shown in Table 2), silicon-doped carbon electrode materials containing silicon nanoparticles for batteries with different oxidation degrees are prepared. The doping amount of silicon nanoparticles for batteries is 20% of the total weight of the silicon-doped carbon electrode materials. Taking the preparation of the half-cell of Example 7 as an example, the silicon-doped carbon electrode material is mixed with a conductive agent, a binder, and a solvent to form a slurry. Then, the slurry is applied to a current collector, and dried, rolled, and slit to form a silicon-doped carbon anode. Then, the silicon-doped carbon anode is assembled with lithium metal, a separator, and an electrolyte to form the half-cell of Example 7. The manufacturing methods of the half-cells of Comparative Example and Example 8 are similar to those of the half-cell of Example 7, but with the following differences: the comparative example uses non-oxidized silicon nanoparticles, and Example 8 uses silicon nanoparticles for batteries that are more highly oxidized than Example 7 (i.e., the thickness of the silicon oxide layer of Example 8 is greater than that of Example 7).

[0058] 3.2 Capacity Analysis and Results

[0059] 3.2.1 Activation test

[0060] The silicon-doped carbon anode half-cell was subjected to three charge-discharge cycles at a constant current rate of 0.1 C. From the data of the first charge-discharge cycle, the first discharge capacity, first charge capacity, and first coulombic efficiency could be obtained. The results are shown in Table 2.

[0061] 3.2.2 Cycle life test

[0062] The silicon-carbon negative electrode half cell is subjected to 200 charge-discharge cycles at a constant current rate of 0.5 C, and the capacity retention is calculated. The results are shown in Table 2.

[0063] [Table 2]

[0064] As can be seen from Table 2, when there is no silicon oxide layer on the silicon surface layer (Comparative Example), the initial discharge / charge capacity of the formed silicon-doped carbon electrode is higher than that of Examples 7 and 8, which have a silicon oxide layer on the silicon surface layer. This is because the capacity of silicon oxide is lower than that of silicon, so the overall capacity is lower after forming the silicon-doped carbon electrode. Also, as can be seen from Table 2, after 200 charge / discharge cycles, the capacity retention of the silicon-doped carbon electrodes of Examples 7 and 8 (with a silicon oxide layer on the silicon surface) is higher than that of the silicon-doped carbon electrode of the Comparative Example (without a silicon oxide layer on the silicon surface), which indicates that the silicon oxide layer on the silicon surface can effectively suppress the volume expansion of the internal silicon, since the capacity retention is related to the thickness of the silicon oxide layer on the silicon surface.

[0065] As described above, in the method for producing silicon nanoparticles for batteries of the present invention, the addition of a dispersant makes it difficult for silicon nanoparticles to bond or aggregate, preventing excessive viscosity from affecting the grinding, thereby promoting the refinement of silicon raw materials. The addition of an alkaline solution allows the surface of the silicon nanoparticles for batteries to have a silicon oxide layer, thereby suppressing the volume expansion of the silicon nanoparticles for batteries. The silicon-doped electrode material prepared by the silicon nanoparticles for batteries of the present invention can effectively improve its capacity retention rate under multiple charge-discharge cycles.

[0066] It will be appreciated by those of ordinary skill in the art that various modifications and variations may be made to the disclosed embodiments without departing from the scope or spirit of the invention. In view of this, it is intended that the present invention cover modifications and variations that come within the scope of the following claims and their equivalents. [Industrial Applicability]

[0067] The silicon nanoparticles for batteries of the present invention can be applied to form silicon-doped electrodes, which have excellent capacity retention upon multiple charge / discharge cycles, thereby extending the service life. [Explanation of symbols]

[0068] S102, S104, S106, S108, S110 steps

Claims

1. mixing a dispersant and a solvent to form a dispersion; adding the dispersion, grinding media, and silicon feedstock to a grinder; carrying out a milling process to form silicon nanoparticles having an average particle size of less than 200 nm; Removing the silicon dispersion containing the silicon nanoparticles; adding an alkaline solution to the silicon dispersion to form silicon nanoparticles for batteries; wherein each surface layer of the silicon nanoparticles for batteries is a silicon oxide layer.

2. The method according to claim 1 , wherein the silicon raw material is a recycled silicon material.

3. 2. The method according to claim 1, wherein the dispersing agent is at least one selected from the group consisting of polyethylene glycol, polyvinylpyrrolidone, triethylhexyl phosphate, sodium lauryl sulfate, methylpentanol, cellulose derivatives, polyacrylamide, and polyethylene glycol fatty acid.

4. The method according to claim 1 , wherein the solvent is water, an alcohol solvent, or a ketone solvent.

5. 2. The method according to claim 1, wherein the amount of the dispersant added to the pulverizer is 10 to 50 parts by weight per 100 parts by weight of the silicon raw material.

6. 2. The method according to claim 1, wherein the grinding media are spherical in shape and have an average particle size of 100 to 500 nm.

7. 2. The method according to claim 1, wherein the amount of the grinding medium added is 100 to 500 parts by weight per 100 parts by weight of the silicon raw material added.

8. The method according to claim 1 , wherein the alkaline solution is a lithium hydroxide solution, a sodium hydroxide solution, or a potassium hydroxide solution.

9. 2. The method according to claim 1, wherein the amount of the alkaline solution added is 0.1 to 5 parts by weight per 100 parts by weight of the silicon nanoparticles added.

10. 2. The method according to claim 1, wherein the grinding process is a wet ball mill method, and the grinding time of the grinding process is 2 to 6 hours.

11. 2. The method according to claim 1, wherein the ratio of the particle diameter of the silicon nanoparticles for batteries to the thickness of the silicon oxide layer is 3:1 to 40:

1.

12. The method according to claim 1, wherein the silicon oxide layer has a thickness of 5 to 30 nm.

13. Providing the silicon nanoparticles for batteries obtained by the manufacturing method of claim 1; mixing the silicon nanoparticles for the battery with an active material; spray granulation and calcination to obtain the silicon-doped electrode material; wherein the active material is a carbon material, a metal element, or a metal alloy compound.

14. The method according to claim 13, wherein the content of the silicon nanoparticles for batteries is 1-40 wt% based on the total weight of the silicon-doped electrode material.

Citation Information

Patent Citations

  • Nanometer silicon-carbon composite material, preparation method, application and lithium ion battery

    CN112713274A

  • Anode active material for lithium secondary cell, method for manufacturing the same, and lithium secondary cell equipped with anode active material

    JP2010140901A

  • Method for producing silicon nanoparticle

    JP2018039695A

  • Fine particle, method for producing the same, and lithium ion secondary battery

    JP2019043821A

  • Silicon or silicon alloy, composite active material for lithium secondary battery containing the same, and manufacturing method thereof

    JP2021180124A